Analysis of Daily Exam Answers on the Curriculum 2013 Topic Distribution and Management Natural Resources at Pertiwi 1 High School in Padang - Syukriyah Syukriyah; Ahyuni Ahyuni; Syafri Anwar; Surtani Surtani (CV. Pusdikra Mitra Jaya, 2024)
This research aims to find out how teachers assess essay questions that contain elements of analysis and to find out students' answers to essay questions that contain analysis on the distribution and management of natural resources on 2013 curriculum. This research uses mixed research methods. The population in the study was all 11th grade of SMA Pertiwi 1 Padang. The sampling technique in this research used a total sampling technique. The total population is 101 people, while the sample size is 101 people. The data collection techniques used were observation, interviews and documentation. The results of this research show that some teachers do not understand how to assess essay questions that contain elements of analysis on material on the distribution and management of natural resources and that most students do not understand the answers to essay questions that contain analysis. This is based on the lack of complexity in the content of geographic concepts that can be linked in creating questions and answering essay questions that contain elements of analysis on the distribution and management of natural resources.